An Electro-Optical Technique For The Measurement Of Temperature Of High Potential Bodies. - Ajmal, Ms T; Rehman, Mahfoozur; Prasad, D; Saad, M R (2006)

(untitled)
In this paper we have presented a low cost, simple and robust mechatronic system for the measurement of temperature in extreme conditions. It is specially designed for the protection of high potential parts of power transformers and switch gears under faulty operating conditions.